UJI AKTIVITAS ANTIOKSIDAN DARI DAUN CENGKEH (Eugenia Carryophyllus) DENGAN METODE DPPH - Rorong, Johnly (Sam Ratulangi University, 2008)
Clove (Eugenia carryophyllus) is a traditional food ingredient characterized by its specific and refreshingaroma. This study was intended to determine the antioxidative effects of clove leaves. Clove leaves wasextracted sequentially with hexane, methanol and ethanol. The antioxidative effects of the extracts weredetermined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging and reducing power assay. Total phenoliccontent of ESME extracts the highest compared with EHS and EEM were 0,851; 1,8575 and 1,237 mg/kgrespectively, which expressed as gallic acid equivalent. The addition of methanol extracts of clove leavesin the reaction mixture showed the highest scavenging activity in 1,1-diphenyl-2-picrylhydrazyl (DPPH)radical and reducing power. These results suggest that the ethanolic extract of clove leaves containscompounds having antioxidative activitiesÂ Keywords : clove, autooxidation, photooxidation, solvent extraction, DPPH